Channel Capture in Noisy Wireless Contention-Based Communication Environments - Bartolomeu, Paulo
Nowadays, as in many other domains, wireless communications are a hot topic in Industrial Automation. Nevertheless, their deployment in real-time applications has been mostly conducted in tightly controlled environments, given the potential threats posed by Denial of Service attacks resulting from interference. Hence, the support of communications providing timeliness guarantees in open wireless environments is an important research topic, not only for soft real-time applications, in general, but mainly for real-time applications with demanding timeliness requirements. This paper addresses the challenge of providing real-time communications in open wireless environments, specifically in the 2.4 GHz ISM band encompassing contention-based interference sources. It presents a novel MAC technique named bandjacking, which allows capturing and maintaining a communication medium with bound delay and jitter in the presence of interference produced by contention-based communication technologies. Furthermore, a proof of concept addressing the proposed technique is experimentally validated through a set of trials, demonstrating the feasibility of bandjacking for the support of real-time wireless communications in open environments.